PANCASILA AS A PILLAR OF DIGITAL ETHICS: FACING SOCIAL CHANGE IN THE ERA OF TECHNOLOGY AND INFORMATION IN GENERATION Z - rizqi, salma zaidah (JURNAL SETIA PANCASILA, 2025)
Pancasila as the basis and ideology of the Indonesian nation faces challenges in the digital era, especially in maintaining its relevance amidst social changes that affect generation Z. This generation, with its characteristics of being adaptive to technology, shows a gap between Pancasila values ??and digital behavior. This research analyzes the role of Pancasila as a pillar of digital ethics through literature and case studies. Several strategies are proposed, such as integrating Pancasila values ??in education, strengthening social media ethics, and approaching the LGBT phenomenon, to strengthen the implementation of Pancasila values ??in the digital life of the younger generation.